Informal philosophy - Stroll, Avrum, 1921-2013 (Rowman & Littlefield Publishers, 2009)
Informal Philosophy provides an original look at how we should understand and teach philosophy. Avrum Stroll persuasively argues that philosophy should be evaluated using its own methodology and should not merely mimic formal scientific analysis, because while modern science does inform our philosophical views about man and his place in nature, it does not solve philosophical problems. Stroll effectively makes the case for the use of informal philosophy--that is, an approach guided by common sense, appealing to ordinary discourse, and employing a context-driven line of inquiry--to answer philoso.